THE UNIQUENESS OF PAMBIWARA`S LANGUAGE IN KAHIYANG AYU AND BOBBY NASUTION`S WEDDING CEREMONY IN SURAKARTA (Kekhasan Bahasa Pambiwara dalam Upacara Pernikahan Kahiyang Ayu dan Bobby Nasution di Surakarta) - Nugraheni Setyaningrum; Wakit Abdullah; Dwi Purnanto (Kantor Bahasa Sulawesi Tenggara, 2018)
The aim of this research is to describe the typicality and uniqueness of master of ceremony ‘pambiwara`s’ language in the panggih temanten procession of Kahiyang Ayu and Bobby Nasution`s wedding ceremony in Surakarta. This research is a qualitative- descriptive with a stylistic approach. The data resources are the text of pambiwara`s speech in the panggih temanten procession of Kahiyang Ayu and Bobby Nasution`s wedding ceremony. The research data are an orthographic transcription of pambiwara`s speech, which is broadcasted live by national televisions. The scrutinizing technique was used to collect the information by scrutinizing the language use of pambiwara. In this context, scrutinizing techniques consist of extracting the uniqueness of language use, encompassing the uniqueness of speech sound and the typicality of morphology in the language of pambiwara. The data was then analyzed through scrutinizing technique and note-taking technique. The result of the research shows that pambiwara in the panggih temanten procession of Kahiyang Ayu and Bobby Nasution`s wedding ceremony has an aesthetic language use, which accentuates on the uniqueness and the typicality of speech sound and morphologic of language. (Penelitian ini bertujuan mendeskripsikan kekhasan bahasa pada bahasa pewara ‘pambiwara’ dalam upacara panggih temanten Kahiyang Ayu dan Bobby Nasution di Surakarta. Penelitian ini berbentuk deskriptif kualitatif dengan pendekatan stilistika. Sumber data data tertulis yang berupa satu teks ‘pambiwara’ dalam upacara panggih temanten Kahiyang Ayu dan Bobby Nasution di Surakarta. Sumber data tersebut berupa sumber data lisan yang disampaikan oleh ‘pambiwara’ yang berasal dari informan. Data berupa transkipsi ortografis ‘pambiwara’ dalam upacara panggih temanten Kahiyang Ayu dan Bobby Nasution di Surakarta yang disiarkan langsung di TV nasional. Teknik dasar yang dipakai adalah menggunakan teknik simak, yaitu teknik mendapatkan data dengan cara menyimak penggunaan bahasa. Dalam hal ini menyadap analisis tentang kekhasan pemakaian bahasa meliputi kekhasan bunyi bahasa dan kekhasan morfologi bahasa dalam bahasa ‘pambiwara’, dan lanjutannya menggunakan teknik simak dan teknik catat. Hasil penelitian ini menunjukan bahwa ‘pambiwara’ dalam upacara panggih temanten Kahiyang Ayu dan Bobby Nasution di Surakarta mempunyai keindahan bahasa yang berfokus pada kekhasan aspek morfologi bahasa.)